2015
DOI: 10.1007/s11015-015-0127-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective Precipitation of Manganese in the Processing of Phosphorus-Bearing Ferromanganese Nodules

Abstract: 669.053 A. A. Dar'in, and N. M. Telyakov A description is given of a technology for processing deep-water ferromanganese nodules in the Baltic Sea with the use of sulfatizing roasting. It is shown that the use of this technology makes it possible to recover manganese in solution without the transfer of phosphorus to the solution as well. Results are reported from studies of the precipitation of manganese by ammonia during the subsequent processing of phosphorusbearing ferromanganese nodules (FMN). The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Sungurov,G.V. Glazkova 587 -the grain yield and the application of mineral fertilizers per 1 hectare of the sowing area of mineral fertilizers is weak because the correlation coefficient r = 0.23, with an increase in the dose of mineral fertilizers per 1 hectare of sowing, the grain yield will increase (Telyakov et al, 2015);…”
Section: Resultsmentioning
confidence: 99%
“…Sungurov,G.V. Glazkova 587 -the grain yield and the application of mineral fertilizers per 1 hectare of the sowing area of mineral fertilizers is weak because the correlation coefficient r = 0.23, with an increase in the dose of mineral fertilizers per 1 hectare of sowing, the grain yield will increase (Telyakov et al, 2015);…”
Section: Resultsmentioning
confidence: 99%
“…Calculation results showed that during roasting manganese sulfatizing process is most probable. Thus, operation of sulphatizing roasting allows to transfer manganese and non-ferrous metals to a water-soluble form, and can be applied to processing of the IMC [17][18].…”
Section: Methodsmentioning
confidence: 99%
“…Sulfate formation is determined by the temperature and composition of the gas phase and is practical if the chemical potential of sulfuric anhydride is greater than the isobaric potential of formation of metal sulfate, and the conditions for selective sulfatization are determined from the ratio RTlnPSO3 < μ < RTlnP'SO3 [15][16].…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…71percent of the total surface of the earth is covered by the oceans, where most of the seafloor reveals mineral deposits of economic interest, such as cobalt-rich crusts, polymetallic hydrometallurgical sulphides, and manganese nodules, reaching 1 to3 billion tonsof majormetal reserves can be found, such as Cu, Ni, Co, Fe and Mn, where the latter is most abundant, with an average content of around 24% [1]. [2]have installed pilot equipment that provides a realistic opportunity for marine nodules extraction, and previous studies,such as those carried out by [3]have already established that hydrometallurgical processes are a viablealternative for processing this mineral matrix, where manganese is obtained by selective precipitation after sulphating roasting.The use of iron as a reducing agent stands out by the abundance and positive results as shown by the authors over the past 20 years [4,5,6]. [7]investigated the effect of working with elemental Fe as a reducing agent at low H 2 SO 4 rates.…”
Section: Introductionmentioning
confidence: 99%